2015
DOI: 10.1111/jcmm.12573
|View full text |Cite
|
Sign up to set email alerts
|

Perinatally administered losartan augments renal ACE2 expression but not cardiac or renal Mas receptor in spontaneously hypertensive rats

Abstract: Since the identification of the alternative angiotensin converting enzyme (ACE)2/Ang-(1-7)/Mas receptor axis, renin-angiotensin system (RAS) is a new complex target for a pharmacological intervention. We investigated the expression of RAS components in the heart and kidney during the development of hypertension and its perinatal treatment with losartan in young spontaneously hypertensive rats (SHR). Expressions of RAS genes were studied by the RT-PCR in the left ventricle and kidney of rats: normotensive Wista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 55 publications
3
90
0
5
Order By: Relevance
“…These opposing actions of ACE and ACE2 were recently reviewed by Smyth, Cañadas-Garre, Cappa, Maxwell, & McKnight, 2019. The AT1R antagonists losartan and olmesartan, commonly applied for reducing blood pressure in hypertensive patients, were shown to increase cardiac ACE2 expression about three-fold following chronic treatment (28 days) after myocardial infarction induced by coronary artery ligation of rats (Ishiyama et al, 2004). Losartan was also shown to upregulate renal ACE2 expression in chronically treated rats (Klimas et al, 2015). In agreement with these observations, higher urinary ACE2 levels were observed in hypertensive patients treated with the AT1R antagonist olmesartan (Furuhashi et al, 2015).…”
Section: Sars-cov-2mentioning
confidence: 99%
“…These opposing actions of ACE and ACE2 were recently reviewed by Smyth, Cañadas-Garre, Cappa, Maxwell, & McKnight, 2019. The AT1R antagonists losartan and olmesartan, commonly applied for reducing blood pressure in hypertensive patients, were shown to increase cardiac ACE2 expression about three-fold following chronic treatment (28 days) after myocardial infarction induced by coronary artery ligation of rats (Ishiyama et al, 2004). Losartan was also shown to upregulate renal ACE2 expression in chronically treated rats (Klimas et al, 2015). In agreement with these observations, higher urinary ACE2 levels were observed in hypertensive patients treated with the AT1R antagonist olmesartan (Furuhashi et al, 2015).…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Contrastingly, patients taking ACEi will have low levels of angiotensin II. There is an upregulation of ACE2 receptors in the kidney and heart in response to ACEi or ARB dosing in rats and humans [46][47][48]. There is no data available on its effect in the alveolar tissue.…”
Section: Ace Inhibitor (Acei) and Angiotensin Receptor-1 Blocker (Arbs)mentioning
confidence: 99%
“…In a different approach, continuous administration of losartan in spontaneously hypertensive rats decreased blood pressure and increased ACE2 expression, suggesting that increased ACE2/Mas activity could be responsible for reductions in blood pressure. Notably, though there was no increase in the renal ACE2 receptor Mas in this study [39]. Adding further uncertainty, another recent study showed that intrarenal alterations of the ACE2/Ang1–7 complex did not significantly modify the course of malignant hypertension in Cyp1a1-Ren-2 transgenic rats, which have abnormally increased activity of the ACE/Ang II/AT1 pathway [40].…”
Section: Hypertensionmentioning
confidence: 67%